Immunological assessment in the detection of perioperative infection in patients operated on for colon cancer (Anales de la Real Academia de Medicina y Cirugía de Valladolid, 2023)
Objective: evaluate the usefulness of quantification in the concentration of leukocytes and lymphocyte subpopulations in blood to identify the presence of anastomotic leak, in patients operated on for colon cancer, even before the appearance of clinical symptoms.Methods: Prospective observational study that consists of extracting different blood samples the day before surgery at 24 hours, 72 hours, and 120 hours post-surgery, to determine the lymphocyte subpopulations in patients that required a scheduled surgical intervention of colon cancer. Results: Sixty-two patients who underwent surgery for colon cancer were analysed for a period of 22 months, 7 of which presenting anastomotic leak. It was observed that presenting 379 cells/mm3 of LTCD4 at 72 hours after surgery indicated an anastomotic leak risk of 19.7 times more than those who had higher figures (p = 0.025). Conclusions: The monitoring of the lymphocyte subpopulations and more specifically of the LTCD4 during the perioperative period in colon cancer can serve to early detect the presence of anastomotic leak.
Keywords: Colon cancer, assessment, immunological, infection, perioperative.